Different Responses to Drug Safety Screening Targets between Human Neonatal and Infantile Heart Tissue and Cardiac Bodies Derived from Human-Induced Pluripotent Stem Cells - Trieschmann, Jan (Stem Cells Int, 2019)
AIMS: Induced pluripotent stem cell-derived cardiomyocytes (iPS-CMs) have become a promising tool in cardiovascular safety pharmacology. Immaturity of iPS-CMs remains an ongoing concern. We compared electrophysiological and contractile features of cardiac bodies (hiPS-CBs) derived from human-induced pluripotent stem cells and human neonatal and infantile myocardial slices relevant for drug screening. METHODS AND RESULTS: Myocardial tissue slices were prepared from biopsies obtained from patients undergoing surgery for hypoplastic left heart syndrome (HLHS) and tetralogy of Fallot (TOF). Electrophysiological features and response to I(k,r) blockade as well as contractile properties were investigated using microelectrodes and isometric force measurements and were compared to hiPS-CBs. Both native myocardial tissue slices as well as hiPS-CBs showed action potential prolongation after I(k,r) blockade, but early afterdepolarisations could be observed in native myocardial tissue slices only. The force-frequency relationship (FFR) varied at lower frequencies and was negative throughout at higher frequencies in hiPS-CBs. In contrast, native myocardial tissue slices exhibited positive, negative, and biphasic FFRs. In contrast to native myocardial tissue slices, hiPS-CBs failed to show an inotropic response to ß-adrenergic stimulation. Although all groups showed ß-adrenergic induced positive lusitropy, the effect was more pronounced in myocardial tissue slices. CONCLUSION: hiPS-CBs were able to reproduce AP prolongation after I(k,r) blockade, but to a lesser extent compared to human neonatal and infantile myocardial tissue slices. Early afterdepolarisations could not be induced in hiPS-CBs. Contractile force was differently regulated by β-adrenergic stimulation in hiPS-CBs and the native myocardium. If used for cardiotoxicity screening, caution is warranted as hiPS-CBs might be less sensitive to pharmacologic targets compared to the native myocardium of neonates and infants.